2006
DOI: 10.1007/s10531-006-9056-3
|View full text |Cite
|
Sign up to set email alerts
|

Site effects outweigh riparian influences on ground-dwelling beetles adjacent to first order streams in wet eucalypt forest

Abstract: In wet eucalypt forest with a rainforest understorey the vegetation adjacent to first order streams does not form a distinct riparian strip. This study investigated the riparian response of terrestrial ground-dwelling beetles adjacent to four such streams in Tasmania, Australia. Beetle assemblages varied more between the four sites than they did with distance from stream within sites, where they exhibited a measurable but subtle riparian response. The extent of the riparian zone varied between the four study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Two beetle species, Baeocera TFIC sp 02 and C. ater, were indicators for continuous upslope forest in the comparison with riparian habitats, while no species was found to be a significant indicator in the comparison between streamside reserves and continuous riparian habitats. Greater similarity of streamside reserve assemblages to continuous riparian than to upslope assemblages is not surprising, because we sampled the interior, more 'riparian' parts of the streamside reserves, and our previous research in the same forest type showed that beetle assemblage composition in the immediate riparian zone differs from that of upslope areas (Baker et al 2007b). In our study, the beetle species commonly collected in streamside reserves were those that were commonly collected in the other unlogged habitats.…”
Section: Streamside Reserve Habitatsupporting
confidence: 54%
See 4 more Smart Citations
“…Two beetle species, Baeocera TFIC sp 02 and C. ater, were indicators for continuous upslope forest in the comparison with riparian habitats, while no species was found to be a significant indicator in the comparison between streamside reserves and continuous riparian habitats. Greater similarity of streamside reserve assemblages to continuous riparian than to upslope assemblages is not surprising, because we sampled the interior, more 'riparian' parts of the streamside reserves, and our previous research in the same forest type showed that beetle assemblage composition in the immediate riparian zone differs from that of upslope areas (Baker et al 2007b). In our study, the beetle species commonly collected in streamside reserves were those that were commonly collected in the other unlogged habitats.…”
Section: Streamside Reserve Habitatsupporting
confidence: 54%
“…In this study, Indicator Species Analysis also found a number of species characteristic of unlogged and regeneration habitats, although some different indicator species were identified compared to those identified in Baker (2006). The present study involved intensive trapping within a smaller study region than our previous studies (Baker 2006;Baker et al 2007b), thus it is possible that certain species were collected from a higher proportion of sites, resulting in significance in the Indicator Species Analysis. …”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations